Language, dreams, and integration: Stories from Canada’s LINC students - Maganaka, Albert (Cahiers de l’ILOB / OLBI Journal, 2025)
This article investigates the dynamics of language learning and cultural integration within the Language Instruction for Newcomers to Canada (LINC) program, focusing on the experiences of three former students who completed Canadian Language Benchmark (CLB) level 5 proficiency in Alberta. Through qualitative interviews and questionnaire responses, this article explores how participation in the LINC program influenced their personal and professional growth, the ways in which the program assisted them, and their future goals in Canada. Drawing on Norton’s theoretical framework of identity, investment, and imagined communities, the research highlights the multifaceted nature of language learning and its implications for immigrant adaptation and socio-economic integration. The findings underscore the students’ resilience, commitment, and aspirations in navigating linguistic and cultural transitions, thus contributing to a deeper understanding of language education and immigrant integration in the Canadian context. Recommendations include diversifying participants, integrating student feedback, and exploring blended learning approaches.